Are they doing better online? a study of social capital and sense of community among selected residential-based online communities in Malaysia - Wan Jaafar, Wan Munira (2015)
Modernization brings about a concern of decline in both social capital and sense of community. Ironically, the emergence of new community – an online community, advanced by the introduction and use of the internet is believed may revised this trend; but the success remains questionable. This research empirically addresses the issues of social capital and sense of community in a study of five selected residential-based online communities with similar attributes. The main methods of data collection were online survey and interviews. 70 online members and 5 informants were involved respectively in the study. Results showed that informants reportedly a significant lower sense of community before they created the community websites. In the present of online communities, the study indicated that sense of community increased to a medium level due to the existance of social capital. Nonetheless, further analysis implied that bonding social capital was more standout than its bridging counterpart. Implications of the generalizations of different types of social capital on the sense of community are discussed.